Effects of fiber reinforcement on adaptation and bond strength of a bulk-fill composite in deep preparations. Issue 4 (April 2020) - Sadr, Alireza; Bakhtiari, Behnoush; Hayashi, Juri; Luong, Minh N.; Chen, Yen-Wei; Chyz, Grant; Chan, Daniel; Tagami, Junji
Abstract: Objective: This study investigated the effect of plasma-treated leno weaved ultra-high-molecular-weight polyethylene fiber placement on gap formation and microtensile bond strength (MTBS) of a bulk-fill composite in deep cavity. Methods: Resin composite molds (3 mm width, 4 mm depth) were treated with Clearfil SE Bond 2 and restored with 3 techniques : (1) Surefil SDR flow (SDR) placed in bulk (BLK), (2) SDR placed in two unequal increments (INC) and (3) SDR placed after an increment of SDR placed with wetted polyethylene fiber (Ribbond Ultra) at the cavity floor (FRC). As a control, the cavities were bulk-filled with SDR and no bonding agent (n = 12). All the specimens were subjected to real-time and 3D imaging by SS-OCT (1330 nm) to calculate the total volume of gap formed (mm 3 ) at the cavity floor and between the composite increments. For MTBS, the occlusal cavities of the similar dimensions (3 × 3 × 4 mm 3 ) were prepared on extracted molars with similar composite placement techniques (BLK, INC and FRC). After 24 h 37 °C water storage, the specimens were sectioned using a diamond saw to create 0.7 × 0.7 mm 2 beams for MTBS, and subjected to bond testing at a crosshead speed of 1 mm/min. Data for both tests was analyzed by one-way ANOVA and multiple-comparisons with Bonferroni correction (α = 0.05). Results: The gap volumes were different among the groups (p < 0.05). The largest cavity floor gaps (mm 3 ) were observed in the control group (2.00 ± 0.08); followed by BLK (0.74 ± 0.20) and INC (0.02 ± 0.01). In FRC, the cavity floor was gap-free in all specimens but some separation was observed between the two increments. MTBS values (MPa) were 13.8 ± 7.6, 31.7 ± 12.5 and 28.3 ± 8.5 for BLK, INC and FRC groups. There was no significant difference between FRC and INC and both were different from BLK (p < 0.05). Significance: Gap formation of the bulk-fill composite at cavity floor was significantly reduced with the placement of a fiber-reinforced increment at the base of the deep preparation. The fiber-reinforced increment acts as a shrinkage stress breaker and protects the bonded interface at deep dentin.